Renewal Concept of Sustainable Tourism Development in Indonesia: Comparative Study of Local Government of Batu City and Probolinggo Regency - Willy Tri Hardianto; Sugeng Rusmiwari; Firman Firdausi (Magister Ilmu Administrasi Publik, 2023)
Development planning and tourism are an inseparable part of the integrated development unity in Indonesia. SDGs demands for sustainable development are a challenge in themselves. Development in Indonesia has an integrated planning system from central to regional government and from region to center. Integrating the SDG's focus as a mandatory aspect of sustainable development, tourism is included as one of the development items. This research uses qualitative methods by comparing the two regions. The concept of sustainable tourism development, namely Pro-Economic Prosperity, Pro-Environmental Sustainability, Pro-Social Justice and Pro-Environment, has not fully answered new problems such as capacity which results in a saturation point in development and change. in leadership in a democratic system for 5 years, and unforeseen circumstances such as natural disasters. Tourism development has been discussed a lot, and some things refer to new variables. This research aims is to find a new concept of sustainable development. Informants from this research used purposive sampling with the informant being the Head of Research and Development at BAPPEDA and the Head of the Tourism Development Section at the Tourism Office in two different regions, namely Batu City and Probolinggo Regency. Primary data uses interview results and secondary data uses official documents from regional organizations. This research produces three new variables in Sustainable Development, namely political sustainability, disaster preparedness, and visitor capacity as aspects that need further consideration. This variable is a new concept in the development of Public Administration Science, especially in the field of Sustainable Development.